Analisis Akuntansi Untuk Likuidasi Korporasi Pada Reksa Dana Terproteksi Tram Terproteksi Prima Xi - Ahmad Gufron; Amrie Firmansyah; Firman Anugrah Firdaus (Kesatuan Press, 2019)
The Imposed Statement of Financing Accounting Standards in Indonesia allow an entity to use another accounting basis other than going concept base when management intends to liquidate the entity or discontinue the trading (PSAK 1, 2015). This study aims to discuss the implementation of accounting standard and the procedures applied by the Reksa Dana Terproteksi TRAM Terproteksi Prima XI management related to its liquidation. This study employs a qualitative approach with using data of TRAM Terproteksi Prima XI’s Audited Financial Statement 31 December 2015 (Liquidation Base) and 2014 (Business Continuity Base) and for the years on that date and Reksa Dana Terproteksi TRAM Terproteksi Prima XI’s Prospectus. Therefore, it could be seen the relation to the imposed accounting standard and liquidation procedures regulated in Indonesia. This study concludes that Reksa Dana Terproteksi TRAM Terproteksi Prima XI apply FASB Accounting Standards Codification Topic 205 on Liquidation Basis of Accounting in the liquidation process. Also of terms of corporate liquidation procedures, Reksa Dana Terproteksi TRAM Terproteksi Prima XI implements more detailed procedures that the Act number 47 of 2007 which only regulates the procedure of liquidation in practice. It could be seen from Reksa Dana Terproteksi TRAM Terproteksi Prima XI’s Prospectus which further explains the obligations of investment managers in the liquidation process compared to the role of the liquidator itself and reporting the results of liquidation and the distribution of proceeds of liquidation to the Financial Services Authority.